An energy‐efficient history‐based routing scheme for opportunistic networks. (28th May 2015) - Dhurandher, Sanjay K.; Sharma, Deepak Kumar; Woungang, Isaac; Saini, Aakanksha
Summary: In opportunistic networks (Oppnets), nodes rely on contact opportunities between them to exchange information with each other. Routing and forwarding in Oppnets remains a challenging task because of the limited energy and bandwidth constraints. Various routing protocols for Oppnets have been proposed in the literature, but only few of them have explicitly investigated the energy issue. In this paper, some improvements in the already existing history‐based prediction for routing protocol for infrastructure‐less Oppnets (so‐called HBPR) is suggested so as to make it energy efficient. The proposed energy‐efficient HBPR protocol (EHBPR) addresses the energy constraints in HBPR and reduces the number of packets transferred in the network, which in turn results to a reduction in the nodes' energy consumption. Through simulations, the performance of EHBPR in terms of energy consumption is compared against the HBPR and the energy‐efficient n‐epidemic routing protocol. The results show that (1) EHBPR consumes 14.66% less energy than HBPR (respectively 13.14% less energy than n‐epidemic); (2) EHBPR generates 67.4% less dead nodes compared with HBPR (resp. 66.33% less dead nodes compared to n‐epidemic); and (3) EHBPR yields 77.86% less overhead ratio compared with HBPR (resp. 84.49% less overhead ratio compared with n‐epidemic). Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This paper proposes an energy‐aware version of the history‐based prediction for routing (HBPR) protocol for infrastructureless opportunistic networks. The proposed protocol is shown to consume 14.66% less energy than HBPR and 13.14% less energy than the n‐epidemic routing protocol.